Isolated Rheumatoid Nodules: A Diagnostic Dilemma - Michael Gale; Erin Gilbert; David Blumenthal (Case Reports in Medicine)
We present a 27-year-old male with multiple nonpainful soft tissue masses over several metacarpals, bilateral elbows, the left wrist, and both knees since the age of 4. Physical exam was significant for firm, nonmobile, nodular growths over the extensor surfaces of bilateral elbows and knees and on the 2nd and 5th metacarpal phalangeal joints. Laboratory studies revealed an unremarkable rheumatoid factor, negative ANA screening and normal joint radiographs. Differential diagnosis included subcutaneous granuloma annulare (SGA), seronegative rheumatoid nodule, and calcinosis cutis. Biopsy is the only method to distinguish benign rheumatoid nodules from SGA. This case illustrates the importance of biopsy in diagnosis, an awareness of the potential complications, and the need for good follow-up.